Medication Error: An Overview - Ramesh, S.; Manimegalai, S.; Priya, P. M. (Innovational: Journal of Nursing and Healthcare, 2024)
Medication is prescribed by health-care professional who is mostly used to treat and cure a disease or illness as well as to treat any medical condition. For example, antibiotics are given to cure a bacterial infection, analgesics to relieve pain. However, an error of medication may occur at any point during the medication use process and in any setting. Medication errors are adverse effects that can be prevented and can be defined as a failure in the treatment process that leads to or has the potential to harm the patient. The health-care professional especially the staff nurse holds the responsibility of serving medication should always be aware and alert when giving medication to the patient. Registered nurses have a key role in discovering and correcting medication errors. According to Hariati Johari (2017), in the Journal of Nursing and Health Science mentioned that patient safety is a common goal for every health-care provider and one of the major issues for safety is medication error. As a nurse, we should avoid the occurrence of medication errors to prevent serious damage and adverse effect on the patient. Medication errors are the single most preventable cause of harm to the patient. They are committed by doctors, pharmacists, nurses, caregivers, manufacturers, and the patient itself. Such events may be related to professional practice, health-care products, procedures, and systems, including prescribing, order communication, product labeling, packaging, and nomenclature, compounding, dispensing, distribution, administration, education, monitoring, and use (Samsiah et al., 2016).